Nurses' use of pliable and directed strategies when encountering children in child and school healthcare. (March 2017) - Harder, Maria; Enskär, Karin; Golsäter, Marie
Nurses in Swedish child and school healthcare need to balance their assignment of promoting children's health and development based on the national health-monitoring programme with their responsibility to consider each child's needs. In this balancing act, they encounter children through directed and pliable strategies to fulfil their professional obligations. The aim of this study was to analyse the extent to which nurses use different strategies when encountering children during their recurrent health visits throughout childhood. A quantitative descriptive content analysis was used to code 30 video recordings displaying nurses' encounters with children (3–16 years of age). A constructed observation protocol was used to identify the codes. The results show that nurses use pliable strategies (58%) and directed strategies (42%) in encounters with children. The action they use the most within the pliable strategy is encouraging (51%), while in the directed strategy, the action they use most is instructing (56%). That they primarily use these opposing actions can be understood as trying to synthesize their twofold assignment. However, they seem to act pliably to be able to fulfil their public function as dictated by the national health-monitoring programme, rather than to meet each child's needs.